Advancing California's microgrid communities through anticipatory energy resilience - Aczel, Miriam R.; Peffer, Therese E. (Frontiers in Climate, 2023)
Given the uncertainty around climate change and the need to design systems that anticipate future needs, risks, and costs or values related to resilience, the current rules-based regulatory and policy frameworks designed for the centralized system of large-scale energy generation and delivery may not be ‘fit for purpose' for smaller scale local installations centered on community microgrids. This research examines regulatory challenges and potential impediments to implementing a multi-customer community-based microgrid in California through discussion of lessons learned in current pilot projects supported in part by initiatives of the California Energy Commission's Electric Program Investment Charge (EPIC). The extent to which regulation has the flexibility to anticipate future needs and risks and support experimentation is evaluated in light of the state's complex and evolving energy system requirements. To illustrate challenges, two case studies of EPIC-supported projects are included. Multiple uncertainties, including future impacts of climate change, energy demands, and advances in technology, highlight the potential need to rethink best approaches to energy regulation. Principles drawn from Resilience Thinking and Anticipatory Regulation are discussed for their potential value in supporting development of new models for community-scale energy production, distribution, and use. Drawing on the experiences of the pilot projects, suggested principles to guide a new regulatory regime specific to microgrids are proposed.